Faktor-Faktor Yang Mempengaruhi Cash Holding Perusahaan Manufaktur Yang Terdaftar Di BEI - Elbert Wiratama, Ardiansyah (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to find the influence that firm size, leverage, and cash flow have on cash holding in manufacturing companies listed on the Indonesia Stock Exchange. This study used a purposive sampling technique with 75 samples of manufacturing companies in Indonesia for 3 years from 2016-2018. Processing and testing of the research model and variable in this study is using Eviews version 10. The results of the study state that firm size and leverage do not have an influence on cash holding while cash flow has a positive influence on cash holding.